From egg to chicken - Legg, Gerald; Scrace, Carolyn; Salariya, David (New York : F. Watts, 1998)
Large illustrations and simple text describe what an egg is made of and how it hatches into a chicken.
Includes index.
"First published in Great Britain in 1997 by Franklin Watts"--P. facing t.p.
L.A. Recommended Foreign Language
2.8
K-3
Keywords: Eggs -- Juvenile literature; Chickens -- Embryos -- Juvenile literature; Chicks -- Juvenile literature; Eggs; Chickens; Eggs; Chickens